PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN PERUBAHAN LABA TERHADAP NILAI PERUSAHAAN - Hermina Lima Baha (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
The purpose of this study was to determine the effect of firm size, institutional ownership, profitability, and earnings changes on firm value in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The population used in this study were 31 companies. While the sample used as many as 16 companies selected by using purposive sampling technique. Multiple linear regression analysis technique is the analysis technique used in this study. Based on the result of the analysis, firm size, institutional ownership, profitability, and earnings changes have a positive effect on firm value.